Pengaruh self-efficacy terhadap perilaku komunikasi seksual orang tua-remaja yang dimediasi oleh niat - Siti Maimunah; Retno Firdiyanti; Riska Puspitasari (Cognicia, 2023)
Adolescence is a time when individuals begin to explore and experiment with sex. Parents play an important role in directing and providing support to adolescents regarding sexuality so that adolescents do not fall into unwanted things. Integrated Behavior Model (IBM) theory is a theory that suppresses individual behavior change determined by intention. Intention cannot be formed without self-efficacy. The purpose of this study was to determine the effect of self-efficacy on parent-adolescent sexual communication behavior mediated by intention. This research uses a quantitative approach with a correlational research design. The subjects of this study were 315 parents who came from various cities in Indonesia and had teenage children aged 14-17 years. Analysis of the data in this study uses mediation analysis to measure that the intention to be a mediator of self-efficacy on sexual communication behavior. The results showed that self-efficacy had a direct effect on the estimate value -0.037  and indirectly or through the intention on parent-adolescent sexual communication behavior with an estimate value 0.013. It is also hoped that parents can increase the desire to engage in sexual communication with their teenagers. Keywords: Intentions, self-efficacy, sexual communication, sexual communication behavior